Modelling of deposition and erosion of injected WF6 and MoF6 in TEXTOR. (August 2017) - Kirschner, A.; Kreter, A.; Wienhold, P.; Weckmann, A.; Pospieszczyk, A.; Ding, R.; Borodin, D.; Brezinsek, S.; Sergienko, G.; Rubel, M.; Linsmeier, Ch.; ,
Highlights: MoF6 and WF6 injection experiments in TEXTOR have been modelled with the ERO code. Modelled amounts of deposited Mo and W are significantly larger than measured ones. In-situ enhanced erosion of deposited Mo and W has to be assumed in ERO. Enhanced erosion factors are about 10 for Mo and 20 for W. Sputtering of W and Mo is dominated by impurities (C, O and self-sputtering). Abstract: Tracer injection experiments in TEXTOR with MoF6 and WF6 lead to local deposition of about 6% for Mo and about 1% for W relative to the injected amount of Mo and W atoms. Modelling of these experiments has been done with ERO applying updated data for physical sputtering. The dissociation of the injected molecules has been treated in a simplified manner due to the lack of dissociation rate coefficients. However, with this it was possible to reproduce the observed radial penetration of Mo and W atoms into the plasma. The modelled local deposition efficiencies are about 50% for Mo and 60% for W assuming typical plasma parameters for the experimental conditions used. To reproduce the measured deposition efficiencies an enhancement factor for the erosion of deposited Mo and W has to be assumed (∼10 for Mo and ∼25 for W). Due to the rather low electron temperature Te of these plasma conditions (Te ∼15 eV at the location of injection), Mo and W are mostly sputtered by impurities whereas sputtering due to deuterium is negligible. A parameter study applying larger electron temperature leads to increased sputtering and thus to reduced local deposition efficiencies of about 30% for Mo and 5% for W. Though, even under these conditions enhanced erosion, albeit with reduced enhancement factors, is needed in the modelling to obtain the small measured deposition efficiencies.